2013
DOI: 10.1039/c3sm52168k
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-isopropylacrylamide) microgels at the oil–water interface: adsorption kinetics

Abstract: Understanding the adsorption behaviors of soft poly(N-isopropylacrylamide) (PNIPAM) microgels to the oil-water interface has become increasingly important both in terms of fundamental science and applications of microgels as multi-stimuli responsive emulsion stabilizers. In the present work, we used pendant drop tensiometry to trace the evolution of oil-water interfacial tensions. We investigated two PNIPAM microgels with different cross-link density as well as poly(styrene-co-NIPAM) particles. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
123
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(133 citation statements)
references
References 59 publications
(209 reference statements)
9
123
1
Order By: Relevance
“…This result shows that the negative charge density of S/N 1 and S/N 8 is greater compared to that of PNIPAM microgel particles, with a nominal zeta potential -20 mV at a temperature below the VPTT. 18,28 The significantly more negative charge density of S/N 1 and S/N 8 particles is possibly due to residual sulfate groups, originating from the decomposition of initiator KPS. It is well documented that below the VPTT, PNIPAM particles adopt a core-corona structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result shows that the negative charge density of S/N 1 and S/N 8 is greater compared to that of PNIPAM microgel particles, with a nominal zeta potential -20 mV at a temperature below the VPTT. 18,28 The significantly more negative charge density of S/N 1 and S/N 8 particles is possibly due to residual sulfate groups, originating from the decomposition of initiator KPS. It is well documented that below the VPTT, PNIPAM particles adopt a core-corona structure.…”
Section: Resultsmentioning
confidence: 99%
“…attributed to the addition of styrene to NIPAM. 33 Because PNIPAM is amphiphilic, even at temperatures above PNIPAM's VPTT, 24 S/N 1 particle can be described as a particle with PSrich dense core and PNIPAM-rich loose shell in water, 28 while S/N 8 particle is PS-rich core with a negligible thin PNIPAM periphery layer at the particle surface, as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon pH induced protonation of charged groups inside the microgels, particles became more dense as well as less connected, their performance as interfacial stabilizer deteriorated [37,44,45]. Upon protonation of charged groups, also the elastic response of the interface as probed by dilational rheology decreased [39]. In accordance with the latter observations, Destribats et al…”
Section: Viscoelastic Properties Of Interfaces Stabilized By Soft Parmentioning
confidence: 70%
“…These soft particles are found to be excellent stabilizer for various types of oil-in-water emulsion [37]. There are some literature reports on water-in-oil emulsions stabilized by microgels, however, the microgels were found to be swollen by the oil phase [38,39]. It was concluded that alteration of the interfacial properties of the microgels by solvent uptake was responsible for the microgels ability to stabilize water-in-oil emulsions [37,38].…”
Section: Structure Of Emulsion Droplets Stabilized By Soft Particlesmentioning
confidence: 99%